Changing Perceptions of Buddhist Meditation in the West - Shaw, Sarah (The Journal of International Association of Buddhist Universities (JIABU), 2019)
I found myself with no money, no friends and a large dose of homesickness, and ended up staying in a Buddhist monastery in Bangkok for six weeks. I lived with the monks, meditating for eight hours a day. And, to my surprise, this turned out to be the best thing that had ever happened to me…..in the monastery, with no other option but to sit and at least try to meditate, I slowly found that I could sit for longer and longer, sometimes more than an hour.